Answer:
26/33
Step-by-step explanation:
The process is:
0.787878
78.7878
78/99x then simplify
Answer:
If y(x-y)^2=x, then int1/(x-3y)dx is equal to (A) 1/3log{(x-y)^2+1} (B) 1/4log{(x-y)^2-1} (C) 1/2log{(x-y)^2-1} (D) 1/6 log{(x^2-y^2-1}
Step-by-step explanation:
Let
x-----------> first <span>odd integer
x+2--------> second consecutive odd integer
x+4-------> third consecutive odd integer
we know that
(x+4)</span>²=15+x²+(x+2)²-------> x²+8x+16=15+x²+x²+4x+4
x²+8x+16=19+2x²+4x-------> x²-4x+3
x²-4x+3=0
using a graph tool----------> to calculate the quadratic equation
see the attached figure
the solution is
x=1
x=3
the answer is
the first odd integer x is 1
the second consecutive odd integer x+2 is 3
the third consecutive odd integer x+4 is 5
Answer:
Notation Rule A notation rule has the following form ry−axisA → B = ry−axis(x,y) → (−x,y) and tells you that the image A has been reflected across the y-axis and the x-coordinates have been multiplied by -1. Reflection A reflection is an example of a transformation that flips each point of a shape over the same line.
Step-by-step explanation: